Analisis Yuridis Putusan No.87/Pdt.G/2020 PN.Bdg Tentang Perceraian yang disebabkan Salah Satu Pihak Pindah Agama di Pengadilan Negeri Bandung - Mardius, Mardius; Putra, Wiwin; Supeno, Supeno (Universitas Batanghari Jambi, 2024)
Marriage cannot be separated from the religious aspect, especially when Law No.1 of 1974 concerning Marriage emphasizes the importance of the religious aspect in the conditions for the validity of a marriage as regulated in Article 2 paragraph (1)